Frequency of Injury Events in New Zealand Compared with the Available E-Codes - Langley, J. D. (Methods of Information in Medicine, 1987)
The frequency of injury events in New Zealand is compared with the distribution of E-codes in the International Classification of Diseases which are used to.describe the circumstances of injury. It is shown that the allocation of codes bears little relationship to the nature and burden of fatal and non-fatal injury events. Common events such as falls are the least adequately addressed by the coding frame. The combining of some codes together with the removal of codes E930-E949 and treatment of intent by a separate code would facilitate an allocation which more closely reflects the distribution of injury events and the provision of information more relevant to injury prevention.
Keywords: E-Codes; ICD; Injuries; Accidents